2018
DOI: 10.1111/eos.12573
|View full text |Cite
|
Sign up to set email alerts
|

Failure loads of all‐ceramic cantilever fixed dental prostheses on post‐restored abutment teeth: influence of the post presence and post position

Abstract: The influence of a fiber post‐restored abutment tooth on the load capability of a three‐unit zirconia framework cantilever fixed dental prosthesis (cFDP) was evaluated after simulated clinical function. Human lower sound premolars (n = 64) were distributed, in equal numbers, to four experimental groups: two vital abutment teeth (group I; control); mesial abutment tooth post‐restored (group II); distal abutment tooth post‐restored (group III); and mesial and distal abutment teeth post‐restored (group IV). All s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…These results are in accordance with the findings of Naumann et al [19] who, in their research, have found that, in Germany, there is a preference for fiber post systems. Based on the results of the study realized by Sterzenbach et al [20], adhesive postandcore restoration of non-vital teeth using a proper ferrule design improves their reliability in serving as abutment teeth for prosthetic reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with the findings of Naumann et al [19] who, in their research, have found that, in Germany, there is a preference for fiber post systems. Based on the results of the study realized by Sterzenbach et al [20], adhesive postandcore restoration of non-vital teeth using a proper ferrule design improves their reliability in serving as abutment teeth for prosthetic reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Ezen anyagok befolyásolják a szinterezési, mechanikai tulajdonságokat. Az adalékok növelésével növekednek a kristályméretek és csökkennek a keménységi, törési szilárdsági értékek [9,11,12,13].…”
Section: Bevezetésunclassified